2017
DOI: 10.1111/liv.13545
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐short bowel is an independent risk factor for liver fibrosis in adults with home parenteral nutrition

Abstract: Background & Aims: Intestinal failure-associated liver disease is rare in adults and risk fac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…In this issue of Liver International , Cazals‐Hatem et al reported their study of 32 adults who received PN, per the new ESPEN guidelines, and underwent liver biopsy. In this study, ultra short bowel (<20 cm of residual small intestine) and alcohol consumption are associated with significant liver fibrosis . Previous studies have correlated liver derangement, namely abnormal function and elevated transaminase activity levels, with short residual small intestine, but this is the first study to consistently incorporate histology .…”
Section: Serial Liver Biopsies In Patients With If‐ald Who Received Imentioning
confidence: 86%
See 4 more Smart Citations
“…In this issue of Liver International , Cazals‐Hatem et al reported their study of 32 adults who received PN, per the new ESPEN guidelines, and underwent liver biopsy. In this study, ultra short bowel (<20 cm of residual small intestine) and alcohol consumption are associated with significant liver fibrosis . Previous studies have correlated liver derangement, namely abnormal function and elevated transaminase activity levels, with short residual small intestine, but this is the first study to consistently incorporate histology .…”
Section: Serial Liver Biopsies In Patients With If‐ald Who Received Imentioning
confidence: 86%
“…It remains unclear if the aetiology of intestinal failure is related to the risk of liver disease. In Cazals‐Hatem et al's article, no association was found; however, this result should be considered with caution as few cases represented each aetiology, and only 2 were inflammatory (Crohn's colitis) . Another study has suggested higher risk of liver disease in patients with inflammatory disorder‐related intestinal failure …”
Section: Serial Liver Biopsies In Patients With If‐ald Who Received Imentioning
confidence: 92%
See 3 more Smart Citations